Sensing the energetic status of plants and ecosystems. (September 2015) - Peñuelas, Josep; Bartrons, Mireia; Llusia, Joan; Filella, Iolanda
<x xml:space="preserve">Abstract</x> The emerging consistency of the relationship between biochemical, optical, and odorous signals emitted by plants and ecosystems offers promising prospects for continuous local and global monitoring of the energetic status of plants and ecosystems, and therefore of their processing of energy and matter.